ADTU-02 V565, a novel oral anti-TNF domain antibody, reduces colonic mucosal inflammation in patients with UC. (8th June 2018) - Parkes, Gareth; Nurbhai, Suhail; West, Mike; Ray, K; MacDonald, Tom; Vossenkaemper, Anna; Crowe, S
Abstract : Introduction: Monoclonal antibodies to TNF transformed treatment options for patients with Inflammatory Bowel Disease (IBD). V565 is a novel oral anti-TNF domain antibody (Vorabody) engineered to be resistant to intestinal proteases. It is in development as a potential oral treatment for IBD. In vitro it suppressed phosphorylation of tyrosine kinases and signalling proteins and inhibited the release of inflammatory cytokines following culture with biopsies taken from patients with CD (Crowe et al. 18th International Congress of Mucosal Immunology, July 19–22 2017, Washington DC, USA). It was safe and well tolerated after high single and multiple doses in healthy volunteers and patient volunteers with CD and resulted in high concentrations of active drug in ileal fluid and faeces. Aims & Methods: This open label study was designed to demonstrate that V565 enters GI mucosa and exerts a beneficial effect on inflammatory processes following oral dosing for 7 days to patients with Ulcerative Colitis. Patients with a Mayo score of 3–10 including an endoscopy score of ≥1 had up to 7 days of oral dosing with 555 mg tid V565. Sigmoidoscopy with biopsies was performed before and after the dosing period. The primary outcomes of interest were presence of V565 in the mucosa and reduction from baseline in phosphorylation of tyrosine kinases and signalling proteins. Detection of V565 was determined by immunohistochemistry. Phosphorylation was determined using PathScan RTK signalling arrays (Vossenkaemper et al 2014. Gastroenterology 147:172–83). Results: Five patient volunteers were treated: Due to visit scheduling, most received 6 days treatment. Presence of V565 was confirmed in the inflamed lamina propria and co-localised with CD14 +macrophages in post-treatment biopsies. Overall phosphorylation of the panel of kinases and signalling proteins was reduced by approximately 50% in four of the five patients. There were no treatment induced ADAs. Conclusion: V565, an oral anti-TNF domain antibody engineered to be resistant to intestinal proteases, was demonstrated bound to CD14 +macrophages in the lamina propria of UC patients and resulted in inhibition of mucosal inflammatory processes after 6–7 days oral dosing. The reduction of 50% in overall phosphorylation is similar to that seen in an earlier study of UC biopsy cultures with infliximab at a concentration of 67 nM (10 µg/ml), a serum concentration associated with mucosal healing (Ungar et al, Clin Gastroenterol Hepatol. 2016 Apr;14(4):550–557). These results provide encouragement that oral dosing with V565 will be a beneficial oral treatment option for patients with IBD.